Ali Poljska prehiteva Slovenijo? - Černoša, Stanislav (Naše gospodarstvo, 2011)
This paper uses bilateral trade data between Poland and Slovenia as central European countries (CEC-2) and the fifteen European member states (EU-15). A previous study presented at an international conference in Wroclaw2 also introduced the same data. However, whereas the central aim of the previous analysis was to confirm the country-specific hypothesis for Poland and Slovenia as central European countries in trade with the EU-15, the current analysis shows the results of the measurement of intra-industry trade between Poland and Slovenia as central European countries in trade with the EU-15 and presents specific factors that define differences in the production structure between both less developed countries. As these two analyses introduce the same bilateral trade data, the results of both studies are completely comparable. The central hypothesis of the current paper is that Poland and Slovenia, which engaged in trade relationships with the generally more developed core EU member states from 1999 to 2008, specialized primarily in the production and export of vertically differentiated lower quality products; during the observed period, they changed only a minority of subsections at the two-digit SITC level, which shows either prevailing specialization in production and export of higher quality products or partial specialization in horizontally differentiated products. More specifically, this paper shows similarities in Polish and Slovenian intra-industry trade specialization-that is, their production structure after 2004, when they became EU member states, which clearly identifies differences in intra-industry specialization adequately explained by differences in GDP per capita3 between these two Central European countries.
Keywords: zunanja trgovina; uvoz; izvoz; investicije; Poland; Poljska; Slovenia; Slovenija